Prognosis and risk factors associated with asymptomatic intracranial hemorrhage after endovascular treatment of large vessel occlusion stroke: a prospective multicenter cohort study. (27th October 2020) - Constant Dit Beaufils, P.; Preterre, C.; De Gaalon, S.; Labreuche, J.; Mazighi, M.; Di Maria, F.; Sibon, I.; Marnat, G.; Gariel, F.; Blanc, R.; Gory, B.; Consoli, A.; et al.
Abstract : Background and purpose: Asymptomatic intracranial hemorrhage (aICH) is a common occurrence after endovascular treatment (EVT) for acute ischemic stroke (AIS). The aims of this study were to address its impact on 3‐month functional outcome and to identify risk factors for aICH after EVT. Methods: Patients with AIS attributable to anterior circulation large vessel occlusion who underwent EVT were enrolled in a multicenter prospective registry. Based on imaging performed 22–36 h post‐EVT, we included patients with no intracranial hemorrhage (ICH) or aICH. Poor outcome defined as a 3‐month modified Rankin Scale (mRS) score 4–6 and overall 3‐month mRS score distribution were compared according to presence/absence of aICH, and aICH subtype using logistic regression. We assessed the risk factors of aICH using a multivariate logistic regression model. Results: Of the 1526 patients included in the study, 653 (42.7%) had aICH. Patients with aICH had a higher rate of poor outcome: odds ratio (OR) 1.88 (95% confidence interval [CI] 1.44–2.44). Shift analysis of mRS score found a fully adjusted OR of 1.79 (95% CI 1.47–2.18). Hemorrhagic infarction (OR 1.63 [95% CI 1.22–2.18]) and parenchymal hematoma (OR 2.99 [95% CI 1.77–5.02]) were associated with higher risk of poor outcome. Male sex, diabetes, coronary artery disease, baseline National Institutes of Health Stroke Scale score and Alberta Stroke Program Early Computed Tomography Score, number of passes and onset to groin puncture time were independently associated with aICH. Conclusions: Patients with aICH, irrespective of the radiological pattern, have a worse functional outcome at 3 months compared with those without ICH after EVT for AIS. The number of EVT passes and the time from onset to groin puncture are factors that could be modified to reduce deleterious ICH. Abstract : In a prospective multicenter cohort study, asymptomatic intracranial hemorrhages do not seem to be so well named. Patients who suffer asymptomatic intracranial hemorrhages, irrespectively of the radiological pattern, have a worse functional outcome at 3‐months compared with those without intracranial hemorrhage after endovascular treatment for acute ischemic stroke. The number of endovascular treatment passes and the time from onset to groin puncture are factors that could be modified to reduce these deleterious ICH.